Use of Apology Strategies in Emails by Chinese Learners of English: Evidence Based on Naturally Occurring Data - Chen, Ying; Lu, Qi; Wei, Yuxuanjing (Frontiers in Psychology, 2022)
Using a data set of 30 authentic institutional emails written by Chinese college students to their native English teacher, this paper investigated the frequency and combinations of apology strategies used by EFL learners in natural contexts. Drawing on the coding framework adapted from Olshtain and Cohen (1983) and Trosborg (1987), this paper carried out a fine-grained analysis of Chinese EFL learners’ apology behaviors when they offended their teacher for various reasons. Results revealed that the most frequently used strategy was illustrative force indicating devices (IFIDs), and “IFIDs + taking on responsibility” ranked the most frequent combination. Among IFID sub-strategies, an expression of regret had the highest frequency. In addition, a new strategy—request for a chance to repair—was identified, which was used by Chinese learners to show their respectful and pious attitude when a more serious offense was made to their teacher. Findings from the study indicate that Chinese EFL learners tend to use culture-specific apology strategies in academic contexts. This study has pedagogical implications for EFL pragmatics instruction in Chinese contexts and also second language pragmatics instruction tailored for native Chinese learners in English-speaking countries.